(3VeGfGJ GdeMGceI GdYGOdI (B: s (3aj VhA GdfXGe GdCSGSj ddeMceI GdLfGFjI GdOhdjI (B/ s - (3OYGA eMSf eMeO YKeGfs; (3TQja SjO cGeds; (3QSGFd LGeYjIs (3LGeYI GdbGgQIs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3GfJgJ OQGSI VeGfGJ GdeMGceI GdYGOdI ai VhA GdfXGe GdCSGSi ddeMceI GdLfGFjI GdOhdjI Edi MbjbI gGeI (B: (3hgi Cfg HGdQZe ef JWhQ VeGfGJ GdeMGceI GdYGOdI hPjhY eHGOiA Mbhb GdGfSGf (B: (3EdG Cf Pdc GdJWhQ oYQbd ai GdhGbY GdYedi (B: (3fXQG deMGhdGJ GdJSjjS hGdGfMQGa HGdeMceI GdLfGFjI GdOhdjI Yf eSGQgG hYf GdOhQ GdefhW HgG efP HOGjI hVY fXGe QheG GdCSGSi hJYeO GjLGO KZQGJ JSJajO efgG GdOhd GdcHQi GdeSjWQI Ydi eLdS GdCef GdOhdi ai GdeSJbHd (B. (3GdCeQ GdPi Vjb ef fWGb aGYdjI GdeMceI fJjLI dJNha GdYOjO ef GdOhd ef GdJUOjb Ydi GdfXGe GdCSGSi ddeMceI MJi dG jchf Pdc GdJUOjb PQjYI ddJONd ai TFhfgG GdOGNdjI Ch ddVZW Ydi QDSGA gPg GdOhd ef bHd GdOhd GdcHQi hGdJi dG JfXQ EdG deUGdMgG GdNGUI hCf jJe Pdc JMJ ZWGA ef GdTQYjI GdOhdjI (B. (3GdCeQ GdPi CUGH GdcKjQjf eef JYdbJ BeGdge hWehMGJge HGdYOGdI hJWHjb GdbGfhf ef NdGd GfTGA GdeMceI GdLfGFjI GdOhdjI GdOGFeI HNjHI Ced (B. (3hYdi GdQZe ef Pdc jXd GfTGA GdeMceI GdLfGFjI GdOhdjI GdOGFeI NWhI gGeI hGjLGHjI Ydi GdUYjO GdOhdi s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2014s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B336-365s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3fXGe QheG GdCSGSjs; (3GdeMceI GdLfGFjI GdOhdjI s; (3eMGceGJ fhQeHQLs; (3Mb GdUeJ s; (3YdGfjI GdeMGceI s; (3eMceI jhZSdGbjG GdSGHbIs; (3VeGfGJ GdeMGceI GdYGOdI s; (3GdbVGA GdWHjYj s; (3TahjI GdeMGceIs; (3eLdS GdCef s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs